Limb Salvage After Failed Initial Operative Management of Bimalleolar Ankle Fractures in Diabetic Neuropathy. (March 2017) - Vaudreuil, Nicholas J.; Fourman, Mitchell S.; Wukich, Dane K.
Background: Ankle fractures in patients with diabetes mellitus (DM) can be difficult to manage, especially in the presence of peripheral neuropathy. In patients who fail initial operative management, attempts at limb salvage can be challenging, and no clear treatment algorithm exists. This study examined outcomes of different procedures performed for limb salvage in this population. Methods: This study retrospectively reviewed 17 patients with DM complicated by peripheral neuropathy who sustained a bimalleolar ankle fracture and failed initial operative management. Patients were treated with revision open reduction internal fixation (ORIF) (3/17), closed reduction external fixation (CREF) (8/17), or primary ankle joint fusion (3/17 tibiotalocalcaneal fusion with hindfoot nail [TTCN] and 3/17 with tibiotalar arthrodesis using plates and screws [TTA]). Median follow-up was 20 months. Results: The overall rate of limb salvage was 82.3% (14/17). All patients who went on to amputation presented with infection and were treated initially with CREF (3/3). All patients who achieved successful limb salvage ended up with a clinically fused ankle joint (14/14); 9 underwent a primary or delayed formal fusion and 5 had a clinically fused ankle joint at study conclusion after undergoing revision ORIF or CREF with adjunctive procedures. Conclusion: This small study suggests that in this complicated group of patients it is difficult to achieve limb salvage with an end result of a functional ankle joint. CREF can be a viable option in cases where underlying infection or poor bone quality is present. Treatment with revision ORIF frequently requires supplementary external fixator or tibiotalar Steinman pin placement for additional stability. All patients who underwent revision ORIF ended up with clinically fused ankle joints at the end of the study period. Primary fusion procedures (TTA, TTCN) were associated with a high rate of limb salvage and a decreased number of operations. Level of Evidence: Level III, retrospective case series.